BENANG MERAH FILSAFAT INDIA DENGAN TEOLOGI HINDU NUSANTARA PADA AJARAN MIMAMSA DAN YOGA DARSANA DALAM TEKS SIWA DHARMA - I Gede Arum Gunawan (Sanjiwani: Jurnal Filsafat, 2019)
Hinduism has a complete construction of religious teachings, namely: Tattwa (theology, religious philosophy), Susila (ethics), dan Acara (ritual). These three frameworks are an inseparable unity. One of the religious texts of Hindu Nusantara which shows the interrelation of these three Hinduism frameworks is Siwa Dharma manuscript. In the Siwa Dharma text, it is discussed about the elaboration of the theological concept of Siwa Sidhanta which is embodied in actions as outlined in the concept of Tri Kaya Parisudha in this text. It is also discussed about the concept of Panca Yajña as well as the various spiritual goals which are contained in those yajña. As a religious text which belongs to the book of Agama in the codification of Vedas, Siwa Dharma text has a very close relationship with the teachings of Darsana as a form of Hindu religious philosophy. This text is capable of showing the close relationship between the teachings of Darsana with the thinking concept of Hindu Nusantara. This text shows how the philosophical foundation of Darsana is translated into actions and deeds of Hindu Nusantara people. This teaching of Hindu Nusantara theology is very much in line with the ideology and practices of the teaching of Darsana especially Mimasa and Yoga Darsana.